Navigating between Disaggregating Nation States and Entrenching Processes of Globalisation: Reconceptualising the Chinese Diaspora in Southeast Asia - Michael Jacobsen (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
This paper argues that the fluidity that permeates the contemporary international community is driven by especially political and economic globalisation, which has a huge impact of the relationship between the nation and the state. As the individual nation state is increasingly depending on the international community for its economic survival this dependency on the global has as a consequence that it rolls back aspects of national sovereignty thus opening up the national hinterland for further international influences. These developments initiate a process of disaggregating state and nation, meaning that a gradual disarticulation of the relationship between state and nation produces new societal spaces, which are contested by non-statist interest groups and transnational more or less deterritorialised ethnic affiliated groups and networks. The argument forwarded in this article is that the ethnic Chinese utilises these newly created spaces for setting up diasporic like networks thus providing substance for transnational ethnoscapes or nations without states. Keywords: globalisation, nation state, diaspora, ethnicity, Chinese, Southeast Asia
hdl:10398/7394
Keywords: 330